Modern science owes its originality to Islamic science: A historical consideration - Salim, Ssuna; Abdullah, Syahrul Faizaz (2014)
This study aims at analyzing the role of Islamic science as a bench mark in tracing the historical roots of Modern science, whose influence is still felt up to the present day, even though not vividly noticed.This is a qualitative study. It uses a descriptive analytical synthetic approach which is mainly interpretative in the form of textual commentary.The study critically analyzes reports and comments of Muslims as well as Western scholars of history of science in view of the originality of Modern Western Science.The study shows with evidences that modern sciences owes its originality to earlier Muslim contribution to the field of science, which was as a result of their understanding and interpretation of the Quranic teachings.The study notes that the contemporary Muslims generation is not generally exposed to these facts, something that has made them think that Muslims have never and are incapable of any significant contribution to this field.The study recommends that all contemporary Muslims generally and specifically those specializing in the field of science should be exposed to these historical facts, something that will give them impetus, confidence and courage to go back to the roots of their predecessors in making significant and original contribution to the field of science, centered around the Tauhidic view of the Islamic teaching.